Pembuatan Laporan Keuangan Usaha Mikro Kecil Menengah Berdasarkan SAK EMKM : Studi Kasus Di UMKM Eat More – Rumah Pohon, Jagakarsa - Kampono Imam Yulianto; Mayasari; Devvy Noveliza; Dias Adi Darma; Shinta Apriliani; Fitria Sholehah; Rizki Amelia (Prisani Cendekia, 2022)
The community service that we are currently working on with the aim of helping make the process of compiling the financial report of MSME Eat More, the constraints reported by MSME Eat More in preparing financial reports and how financial reports should be made by MSME Eat More in accordance with MSME Standards. This Community Service Design is qualitative in nature by collecting data, interpreting the data, and ending with the history of the MSME owner during the interview. Data and information were collected by means of interviews, documentation and observation. The results of Community Service show that (1) The process of preparing financial reports for Eat More composes simple financial records, (2) Constraints that help Eat More prepare financial reports in accordance with Micro, Small and Medium Enterprises, Macro Financial Accounting Standards (SAK EMKM) .